Assessing the Financial Performance of PT Jaya Konstruksi Manggala Pratama Tbk: a Perspective of Agency Theory - Nasution, Narach Larasati (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to analyze the financial performance of PT Jaya Konstruksi Manggala Pratama Tbk from 2021 to 2024 using trend analysis and agency theory as the theoretical framework. In the context of modern business, the agency problem arises due to conflicts of interest and information asymmetry between managers (agents) and shareholders (principals). Financial trend analysis serves as a tool to evaluate how well management has performed in enhancing the company’s value and achieving operational efficiency. The study employs a descriptive quantitative approach with secondary data obtained from audited financial statements published by the Indonesia Stock Exchange and the company’s official website. The findings reveal that while the company showed improvements in equity growth and a reduction in liabilities, there was a notable decline in total assets and profitability in 2024. These fluctuations suggest potential inefficiencies in operational strategy. From the agency theory perspective, the management demonstrated efforts to align their actions with shareholder interests, particularly through consistent equity increases and profitability in recent years. However, the decline in income and earnings in the final year signals the need for stronger oversight and better incentive mechanisms. This research contributes to a deeper understanding of how agency theory can be applied in evaluating corporate financial performance and governance practices in the Indonesian construction sector.